SIMULATION OF THE INFLUENCE OF VEGETATION ON MICROCLIMATE AND THERMAL COMFORT IN THE CITY OF SÃO PAULO - Spangenberg, Jörg; Shinzato, Paula; Johansson, Erik; Duarte, Denise (Revista da Sociedade Brasileira de Arborização Urbana, 2008)
The microclimates of a park, a square and a street canyon were measured on a summer day in the city centre of São Paulo, Brazil. The field monitoring showed that the park was up to 2°C cooler than the square and the canyon. The effect of adding shading trees to the street canyon was simulated for the same day using the numerical model ENVI-met. The simulations showed that incorporating street trees in the urban canyon had a limited cooling effect on the air temperature (up to 1.1°C), but led to a significant cooling of the street surface (up to 12°C) as well as a great reduction of the mean radiant temperature at pedestrian height (up to 24°C). Although the trees lowered the wind speed up to 45% of the maximum values, the thermal comfort was improved considerably as the physiologically equivalent temperature (PET) was reduced by up to 12°C.